Need Satisfaction Moderates the Association Between Physical Activity and Affective States in Adults Aged 50+: an Activity-Triggered Ambulatory Assessment. Issue 1 (18th August 2016) - Kanning, Martina; Hansen, Sylvia
Abstract: Background: Substantial evidence shows that physical activities of daily living are positively correlated with affective states in middle-aged and older adults. However, people's physical activity decreases when they grow older, and conditions that enhance older individuals' physical activities of daily living are not well understood. Purpose: This study investigated need satisfaction (competence, relatedness, and autonomy) and its moderating effect on the within-subject relation between physical activities of daily living and three dimensions of affective states (valence, energetic arousal, and calmness) based on an ambulatory assessment that used activity-triggered e-diaries. Method: The physical activities of daily living of 68 adults aged 50+ (mean age = 60.1 ± 7.1) were measured objectively for three consecutive days, and need satisfaction and affective states were assessed as a function of the amount of physical activity during the preceding 10 min before the affect measurement (in activity-triggered e-diaries). Hierarchical multilevel analyses were performed. Results: Need satisfaction was significantly and positively correlated with the three dimensions of affective states. Further, physical activities of daily living were significantly associated with energetic arousal and calmness, but not valence. However, when physical activities of daily living were more autonomously regulated, the association of physical activities of daily living and valence became significant and positive. Conclusion: The findings regarding the significant moderating effects of need satisfaction are crucial for interventions aiming to improve the health-enhancing effects of physical activity in adults aged 50+. Positive feelings owing to physical activities in daily living depend on the extent that psychological needs are satisfied.